The role of American intelligence in shaping foreign policy strategies - Artemov, Volodymyr; Ishchenko, Yevhenii; Rusnak, Alexander; Trepak, Viktor; Denysenko, Mykola (Edelweiss Applied Science and Technology, 2024)
The aim of this research is to determine the role of intelligence in shaping the U.S foreign policy by comparing the positions of the government and citizens of the state. The research employed a doctrinal approach, a statistical method, a historical method, and a comparative analysis. The conducted research determined that the priorities of U.S foreign policy are based on achieving and maintaining an advantage over competing countries to ensure national security and a safe, free, and prosperous world. The important role of intelligence in achieving such goals is confirmed through the analysis of the budgets of the U.S. Intelligence Community. The analysis found that the increase in funding correlates with the need to intensify intelligence activities during various critical events, primarily related to the activities of competing states. Comparison of the priorities of the U.S government and citizens regarding foreign policy, in which intelligence plays a leading role, revealed certain differences. These include, in particular, the priorities of citizens who are supporters of different parties. The conducted analysis emphasizes the need to take public opinion into account while developing foreign policy. The practical application of the obtained results lies in the possibility of their advocacy by politicians to adapt communication strategies according to the expectations and requests of voters.